1996
DOI: 10.1007/bf02376773
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of training at moderate altitude versus sea level training in amateur runners

Abstract: After more than 25 years of research of altitude training (AT) there is no consensus regarding either the training programme at altitude or the effects of AT on performance at sea level. Based on a review of the research work on AT, we investigated combined base training and interval training at moderate altitude and compared immediate and delayed effects on sea level performance with those following similar sea level training (SLT). The altitude group (AG, 10 male amateur runners) trained at 2315 m (natural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 20 publications
2
31
0
1
Order By: Relevance
“…It was concluded that several metabolic adaptations to extended exposure to high altitude are similar to those following endurance training at sea-level (Burtscher et al 1996).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…It was concluded that several metabolic adaptations to extended exposure to high altitude are similar to those following endurance training at sea-level (Burtscher et al 1996).…”
Section: Introductionmentioning
confidence: 93%
“…The altitude of 2500 m was chosen because earlier studies demonstrated that the most signi®cant adaptations occur within a range of 2000±2500 m (Holewijn and Meeuwsen 1996). In addition, a review of many recent research studies suggests that the appropriate training altitude ranges between 2000 m and 3000 m (Burtscher et al 1996). It must be stressed that the opinion``the higher the better'' is compromised because the subjects suer severe side-eects.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a review of many recent research studies suggests that the most appropriate training altitudes range between 2,000 m and 4,000 m (Holewijn and Meeuwsen 1996). Even the concept of living low and training high with varying altitudes could be beneficial (Kayser 1994;Burtscher et al 1996;Holewijn and Meeuwsen 1996;Meeuwsen et al 2001;Vallier et al 1996).…”
Section: Designmentioning
confidence: 98%
“…Increasing red cell mass is recognised as a potent means of improving athletic performance (Buick et al 1980;Celsing et al 1987;Jones and Pedoe 1989), and world-class athletes, seeking even the smallest physiological advantage over competitors, spend several weeks at moderate altitude (»2000±3000 m) in an attempt to stimulate red blood cell production and thus improve endurance performance. Whether these relatively brief periods of living at moderate altitude increase red blood cell production in highly trained individuals has yet to be established conclusively, despite more than 25 years of investigation (Burtscher et al 1996). In spite of this equivocal evidence, it has been proposed that athletes who live at moderate altitude, but train near sea level, would experience sucient hypoxic stimulus to ensure an increase in red blood cell production ± the``live high, train low'' principle (Levine et al 1991).…”
Section: Introductionmentioning
confidence: 98%